In a galaxy (no longer) far, far away, The Mandalorian between platformization and processes of celebrification. - Castellano, Simona (Funes. Journal of narratives and social sciences, 2024)
The paper’s main aim is to analyse the television series The Mandalorian, placed within the transmedia narrative ecosystem (Pescatore, 2018) of Star Wars, to reflect on several particularly urgent issues concerning the contemporary mediascape and, more generally, the digital society we live in. Distributed by Disney+ in Italy in March 2020 (2019 in the USA), the series covered by the paper allows us to advance multiple considerations. First, it will enable us to reflect on complex television (Mittell, 2017) and how this has changed regarding renewed spectatorship (Tirino, 2020). Secondly, it allows us to reflect on new modes of consumption, production, and distribution related to the rise of SVOD services and OTT Television (Re, 2017b) and, in this case, the existence of a (proprietary) platform of the Walt Disney Company group. The Mandalorian also allows us to focus on the evolution of transmedia storytelling (within the Star Wars universe or, more generally, within the mediascape in which we live). A further aspect concerns the concept of celebrity: the production’s choice fell on the actor Pedro Pascal to play the Mandalorian; the actor participated in the promotional events linked to the release of the series, but for almost the entire duration of the first season and the second one a helmet and armour cover him. After contextualising the television series, the paper intends to highlight the abovementioned aspects.